Utilization of mechanically recovered poultry meat for the production of shelf-stable chicken patties - Aquino Karen Astrid Ramos; Dumelod, Benelyn Domingo (2003)
ABSTRACT This study was conducted to develop a shelf-stable chicken patty that would utilize mechanically recovered poultry meat. Focus Group Discussions were performed to identify the sensory attributes of a highly acceptable patty. Improvement of existing formulation in terms of juiciness and chewiness were done based on FGD results. Three formulations of chicken patties (coded A, B and C) with varying types of binders were subjected to sensory evaluation for consumer acceptability. Formulation B was chosen over samples A and C based on the ranking test conducted. To improve the shelf-life of the product, different proportions of antimicrobials were added to formulation B, resulting in four treatments: B0 (control), B1, B2 and B3. These were assessed through microbiological examination (both raw and cooked form) and sensory evaluation, performed a day and a week post-production. With the combined effects of storage and antimicrobials, the microbial counts obtained in all treatments were within the BFAD recommended microbiological limits. However, the proportions of antimicrobials in sample B2 proved to be the most effective in inhibiting growth of microorganisms. B1 was considered the most acceptable formulation on the second day after production but B2 was, on the eighth day. The chosen product, B2, was subjected to proximate analysis. The moisture, protein and available carbohydrate contents of the developed patty are higher than those in literature while the fat and fiber contents are lower. The ash content is high possibly due to the elevated levels of calcium and iron in MRPM.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Poultry -- Processing